Technological Implementation in the Brazilian Family Farming Context in Order to Minimize CO2 and CH4 Emissions, a Feasibility Analysis. - Villazón Montalván, Roberth Andrés; Dorow, Reney; de Carvalho Pinto, Cátia Regina Silva (European Journal of Sustainable Development, 2016)
In Biguaçu County, State of Santa Catarina, traditional family farming represents most of the county’s activity. These family farmers carry out a particular land use on which agriculture, forest and energy production are related. These farmers perform fallow agriculture in secondary subtropical forests (Atlantic Forest biome) where, energy production is made in the form of charcoal. As charcoal production is realized in traditional handcrafted kilns, gravimetric yield is meager and greenhouse gases emissions are high. In order to improve this scenario it has been experimentally installed in late 2014 a volatile recovery system (SRV). The SRV installation respond to three main characteristics: to be easily reproducible by others farmers, to have a low initial investment and to be locally adapted. The SRV allows the condensation of the gas fraction during production, obtaining pyroligneous acid (PA). Calculations indicate a PA production potential of about three thousand-liter year. Initial investment is reachable by local farmers and the investment recovery will take five years. The implementation results in a 30% increase in profits, a minimization of 1/8 of total emissions and 15% improve in gravimetric yield. With this basis, the SRV implementation can be considered as a feasible green infrastructure at regional scale. Key-words: Emerging Countries, SME, Technological innovations, Feasibility analysis, CO2 and CH4 emissions, Family Farming.